Peningkatan Motivasi Belajar Matematika Melalui Pembelajaran Guided Note Taking pada Kelas III SD - Eka Fitriana HS; Satriawati Satriawati; Muh. Reski Salemuddin; Perawati Bte Abustang (IAI Muhammadiyah Sinjai, 2021)
This study aims to determine the increase in motivation to learn mathematics on the implementation of Guided Note Taking learning strategies in third grade students of SD Negeri Kassi Makassar City. The type of research used is Classroom Action Research (CAR) which is recycled/cycled with a focus on the implementation of the Guided Note Taking strategy. And the subjects in this study were third grade students of SD Negeri Kassi Makassar City with a total of 29 students. Data collection techniques used are questionnaires, documentation, and observations regarding student learning activities during the learning process. The discussion of the results of the teacher activity research in the first cycle was in the sufficient category (C) while in the second cycle it increased to good (B). Likewise, the student activities in the first cycle were in the sufficient category (C) while in the second cycle increased to the good category (B). The results showed that in the first cycle the motivation to learn mathematics in the class was in the less category (K) and in the second cycle it increased and was in the good category (B). The conclusion of this study is that the application of Guided Note Taking learning strategies can increase the learning motivation of third grade students of SD Negeri Kassi Makassar City.